A new perspective on nature of fire-induced spalling in concrete - Liu, Jin-Cheng; Tan, Kang Hai; Yao, Yao (Construction & building materials, 2018)
•A unified fire-induced concrete spalling theory is proposed.•Fire-induced spalling is categorised into three types according to their distinct governing mechanisms, viz., thermo-hygral, thermo-mechanical and thermo-chemical spalling.•The spalling temperature range, influencing factors and the protective measures for each type of spalling are discussed.•A design concept of ‘multiple defense line against fire-induced concrete spalling’ is introduced based on the unified fire-induced concrete spalling theory. Spalling of concrete is a great potential threat to fire resistance of concrete structures. Understanding the underlying mechanism is important to predict and mitigate this unfavorable phenomenon. Currently, there are two main mechanisms to explain the fire-induced concrete spalling: viz. spalling due to (a) pore pressure buildup or (b) thermal stress. The relative importance of these two mechanisms has been a subject of intense debate in the research community over the past few decades. This paper presents a critical review of conflicting and concordant points on concrete spalling at high temperature and proposes a unified and coherent fire-induced concrete spalling theory. Therein, the authors propose three types of thermal spalling depending on the governing mechanisms: thermo-hygral spalling, thermo-mechanical spalling and thermo-chemical spalling. The criteria to forecast each type of spalling are established and the spalling temperature range for each of them is analysed. The spalling pattern, influencing factors and preventive measures for each type of spalling are also discussed in this paper.